Development of Speech-Communicative Culture of Future Teachers of Primary School in the Conditions of Reforming of Education - Chala, Anna (Pedagogical Discourse, 2017)
In the article the author analyzes the main ways and means of improving speech and communication culture of primary school teachers. Materials of the article is covering one of the urgent problems of training future teachers – the development of speech-communicative culture of primary school teachers in the conditions of reforming of education. The article provides an analysis of the General linguistic situation of the country. Highlights the problem of forming speech and communication culture of future primary school teachers and are recognized as the basic ways and means for its improvement. The publication presents an analysis of the category of «speech culture» as a linguistic and social and educational phenomenon, reveals conceptual framework and technology of its development of future teachers during training in higher education. To increase the development speech and communication culture of primary school teachers the paper proposes a number of measures, among which we determine the most effective. The attention is paid to formation and development of cognitive motives that influence the knowledge and skills of students in accordance with their future profession. It is described how to monitor the development speech and communication culture of future primary school teachers. The proposed method of development management speech and communication culture of future primary school teachers, thereby improving their speech and communication culture, the main tasks of professional training. The problems that require further study are described. Key words: speech-communicative culture, language issue, future primary school teachers, culture of speech, slang, linguistic personality, speech culture, Ukrainian literary language, reform, language education, vocabulary, knowledge of students.